Inductive inference and its natural ground an essay in naturalistic epistemology - Kornblith, Hilary (MIT Press, 1995)
This work presents an account of inductive inference that addresses both its metaphysical and epistemological aspects. The author argues that inductive knowledge is possible by virtue of the fit between our innate psychological capacities and the causal structure of the world.
Keywords: Quine, W. V. -- 1908-2000; Induction (Logic); Inference; Knowledge, Theory of; Naturalism; Schlussfolgern; Evolution; Erkenntnistheorie; Induktion; Naturalismus -- Philosophie